On Preservations and Destructions in the Unconscious: Freud and Bion - Cosimo Schinaia (EJP import test, 2016)
Summary: In Civilization and its Discontents (1930), Freud initially uses the image of the city of Rome in several historical periods (“Roma Quadrata,” “Septimontium,” the Rome enclosed within the Aurelian Walls, etc.) to stress conservative aspects: nothing that has ever taken place has disappeared. This metaphor was abandoned because, according to Freud, the demolitions and replacements of buildings occur during the most peaceful development of a city. Bion in Attacks on Linking (1959) gives prominence to destructions that are not static and are important in the analytic relationship. Moving from Bion’s clinical reflections, it is possible for the analytic couple to work towards achieving recoveries, transformations and creative redistributions[1].
Keywords: Destruction; preservation; Rome; transformation; unconscious